2016
DOI: 10.11152/mu.2013.2066.183.sko
|View full text |Cite
|
Sign up to set email alerts
|

Can diagnostic ultrasound scanners be a potential vector of opportunistic bacterial infection?

Abstract: Ultrasound examinations are recognised as being safe. The greatest epidemiological threat during the performance of examination is the transfer of pathogenic and opportunistic microorganisms between patients and from personnel to patients. Colonization of the skin with opportunistic bacteria of immunocompromised and high risk patients may lead to infection following an ultrasound scan. Aim: To identify and evaluate the strains of bacteria occurring on ultrasound equipment subjected to unexpected control perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
0
13
0
2
Order By: Relevance
“…During the pandemic of COVID-19, attention must be paid at collecting clinical and epidemiological indicators, i.e., respiratory symptoms, fever, recent travel history to area with serious outbreak, or contact with confirmed cases [33]. Patient under investigation (PUI) is defined as a suspected case on the basis of the followings; [1] pneumonia of unknown origin, or [2] fever (≥37.5°C) and/or respiratory symptoms, or [3] epidemiological correlation with the domestic mass outbreak or contact with a confirmed case of COVID-19 and exhibiting fever and/or respiratory symptoms within 14 days. Infection can be confirmed within 90 min by nasopharyngeal swab for detection of viralspecific RNA with real-time reverse transcription polymerase chain reaction (RT-PCR) [34].…”
Section: Detection and Confirmation Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic of COVID-19, attention must be paid at collecting clinical and epidemiological indicators, i.e., respiratory symptoms, fever, recent travel history to area with serious outbreak, or contact with confirmed cases [33]. Patient under investigation (PUI) is defined as a suspected case on the basis of the followings; [1] pneumonia of unknown origin, or [2] fever (≥37.5°C) and/or respiratory symptoms, or [3] epidemiological correlation with the domestic mass outbreak or contact with a confirmed case of COVID-19 and exhibiting fever and/or respiratory symptoms within 14 days. Infection can be confirmed within 90 min by nasopharyngeal swab for detection of viralspecific RNA with real-time reverse transcription polymerase chain reaction (RT-PCR) [34].…”
Section: Detection and Confirmation Of Covid-19mentioning
confidence: 99%
“…The central air conditioning is generally closed vented, and without High Efficiency Particulate Air (HEPA) filtration to arrest very fine particle. There are repeated handling of transducers, machine console, keyboards, touch screens, trackballs, and recording devices [3,4]. Basic knowledge of infection prevention measures is usually lacking among ultrasound providers [5].…”
Section: Introductionmentioning
confidence: 99%
“…Ganz überwiegend fanden sich in den anderen Fällen Koagulase-negative Staphylokokken [28]. Aus Australien wird über Kontaminationen von 60 % aller Schallköpfe nach abdominellen Untersuchungen berichtet [29], aus Polen von 42 -100 % der im Routinebetrieb untersuchten Schallköpfe [30]. Eine aktuelle, europäisch-amerikanische Untersuchung fand Schallköpfe tendenziell stärker mikrobiell kontaminiert als öffentliche Toiletten und Haltestangen in Bussen [31].…”
Section: Mikrobielle Kontaminationunclassified
“…The ultrasound examination involves close contact with a patient, and in the context of COVID‐19, disinfection of the ultrasound probe and machine is crucial, along with appropriate PPE to prevent infection transmission. Previous studies revealed that high‐touch surfaces of the ultrasound machine have a high prevalence of microorganisms 24,25 and hence may be a vector in the transmission of SARS‐CoV‐2. Furthermore, survey and interview‐based studies have highlighted that ultrasound practitioners have a gap in knowledge of basic infection prevention and control (IPC) measures and standardisation is required 26,27 .…”
mentioning
confidence: 99%